Can the evolution of joint savings agreements counter the effect of higher costs of migration on its intensity? - Oded Stark; Marcin Jakubek (University of Bonn, Center for Development Research (ZEF), 2022)
In this paper we consider a population of would-be migrants in a developing country. To begin with, this population is divided into two sets: those who save by themselves to pay for the cost of their migration, and those who pool their savings with the savings of another would-be migrant to pay for the cost. Saving jointly brings forward the timing of migration: funds needed to pay for the migration of one of the co-savers can be accumulated more quickly, enabling him, using his higher income at destination than at origin, to speed up the migration of his co-saver. However, people may hesitate to save jointly for fear that a co-saver who is the first to migrate might fail to keep his part of the agreement. We show that an increase in the cost of migration stimulates the formation of co-financing, joint-saving arrangements that enable would-be migrants to cushion the impact of the increase. The evolution of joint-saving arrangements can create a time window during which the intensity of migration need not decrease: no fewer people (and conceivably even more of them) will migrate during a time interval that follows the increase in the cost. This prediction is at variance with the canonical economic model of migration according to which if migration is costlier, then there will be less of it.
Keywords: D01; D71; D81; D83; D84; D91; F22; G41; O15; 330; Cost of migration; Saving for migration schemes; Evolution of joint saving agreements; Proximity in social space; Revised perception of the risk of joint saving; The intensity of migration